INHIBITORY FACTORS IN ALPINE SKIING TRAINING - Siniša Karišik,; Marko Vasić,; Pekić Spasoje,; Strujić Haris, (Sport Scientific And Practical Aspects, 2025)
Over fifteen years of experience in work with trainees, conducting training in ski school, allowed us to gain clear perspective about the attitude of trainees on first steps in taking up skiing. It was surprising that a significant number of trainees of different age and gender gave up or had intention to give up further training due to factors we are going to present in this paper. In course of training the aforementioned trainees, instructors mainly focused on the sequence of training exercises, demonstration and explanation of specific exercises and skiing techniques but they marginalized certain details which turned out to be essential for the trainees to continue with their training. This demonstrates that skiing training is very complex area and that the instructors ought to listen to and observe the requirements and shape of trainees in addition to the methodic principles of training and skiing expertise. We have detected following inhibitory factors in training: comfort, fear, too high expectations of the instructors and communication. Elimination of these factors would make ski training more suitable for many trainees and a number of trainees who lose motivation and willingness would be reduced. The fact is that sometimes details can be crucial for making changes in positive direction in ski training which is the reason why the instructors must be fully dedicated to the training and educated to notice and eliminate current unwanted factors influencing the trainees